Inoculation of microorganisms and addition of residues to recover a degraded area in the Cerrado, effects after six years' intervention (Research, Society and Development, 2020)
Degraded areas are the result of anthropic action, such as those adjacent to hydroelectric plants (HPP), where the soil is removed for use in the construction of the dam. Without the fertile layer, the exposed subsoil does not contribute to natural regeneration. As a result of the intense degradation, new technologies are required for land vegetation cover and the recovery of ecosystem functions. In this pursuit, we proceeded to inoculation (soil-inoculum) of microorganisms and the addition of residues. After six years, this study aimed to evaluate the chemical and microbiological attributes of the soil, as well as the spontaneous growth of native grasses, considered as indicators in this research. The study was performed in an area degraded by the construction of the HPP, in the city of Selvíria – MS, on the farm of UNESP – Ilha Solteira School of Engineering (Brazil), where the original vegetation was the Cerrado. The experimental design was randomized blocks, in a 2 x 4 factorial scheme, that is, 4 residue treatments in pits (macrophytes – MC; sugarcane bagasse ash – SBA; MC + SBA; and control without residues) and two inoculation treatments (with and without soil-inoculum), with 4 replicates (blocks) and 5 pits per replicate. The soil-inoculum, source of microorganisms, including spores of arbuscular mycorrhizal fungi (AMF), was collected in the preserved Cerrado area. Increases in the levels of P, K, Ca, SB, and V%, with a reduction of Al and greater sporulation of AMF were provided by the addition of soil-inoculum, but not by the residues. After six years of its implementation, small alterations were observed, indicating that the contributions of the residues were quickly exhausted, or that the amount was insufficient for the intense existing degradation.